A13 A HIGH SALT DIET SYNERGIZES WITH UC MICROBIOTA TO INDUCE A PROINFLAMMATORY IMMUNE TONE IN IMMUNOCOMPETENT GNOTOBIOTIC MICE. (4th March 2021) - Santiago Badenas, A; Hann, A; Galipeau, H J; Constante, M; Bercik, P; Verdu, E
Abstract: Background: The exact cause for inflammatory bowel disease (IBD) is unknown, however, there is consensus that a combination of genetic, environmental, and immune factors, participate in its pathogenesis. Recently, high salt diet (HSD) has been shown to increase the severity of experimental colitis through depletion of lactobacilli in specific pathogen-free mice. However, whether HSD-microbiota interaction occurs in mice colonized with microbiota from patients with IBD, is unknown. Aims: Our aim was to determine whether mice colonized with microbiota from patients with active ulcerative colitis (UC), one of two forms of IBD, develop more severe inflammation when fed a HSD. Methods: 10–15 week-old germ-free C57BL/6 mice were colonized with fecal microbiota from a healthy control (HC, n=13) or from a patient with UC experiencing a flare (UC, n=13). Colonized mice were housed in ISO positive cages (Techniplast) in a gnotobiotic facility during the experiment. For each group, half of the mice were kept on a control diet (7004, Teklad) and the other half were fed a HSD (7004 supplemented with 4% NaCl) plus 1% NaCl in drinking water for 3 weeks. At sacrifice, colon tissue was collected for histological analysis, RNA sequencing, and flow cytometry. Fecal samples were collected for lipocalin-2 determination. Results: Colonic polymorphonuclear (PMN) cells were higher in UC compared with HC mice, regardless of diet (p<0.01). In mice fed HSD, UC mice also had higher PMN cell counts than HC mice (p<0.001). Administration of HSD to UC, but not to HC mice, also increased the proportion of α4 + IFNg-producing T cells in the colonic lamina propria, compared with UC mice fed control diet (p<0.01). This was paralleled by higher fecal lipocalin-2 in UC mice fed HSD compared with control diet (p<0.05). Targeted analysis of RNA sequencing data revealed that 7 genes, mainly related to the JAK/STAT pathway (i.e., Stat2, Tyk2, Tlr7 ) were differentially expressed (p≤0.05) between HC and UC mice fed the control diet. A different gene expression signature was found in mice fed HSD compared with control diet, with an increase in proinflammatory genes in UC colonized mice compared to HC colonized mice, such as Il12a and Il6 (p<0.05). Conclusions: Immunocompetent mice colonized with microbiota from a UC patient in flare spontaneously developed a proinflammatory immune tone, which was exacerbated by HSD. The different pattern of gene induction observed in mice colonized with the microbiota from the same UC donor, but fed HSD, suggests independent and synergistic pathways conducive to inflammation. Future studies will explore the preclinical therapeutic effect of novel drug candidates for the inhibition of such pathways. Funding Agencies: CCC